Vygotskij, Tolstoj e la costruzione del senso - Grazia Basile (Rivista Italiana di Filosofia del Linguaggio)
The aim of this paper is to analyze the way in which, according to Vygotskij, human beings form and organize their experiences and, at the same time, develop senses and shared meanings within a linguistic community. In this respect Vygotskij, in his works, often refers to Tolstoy establishing with him a dialogue that helps us to understand some key points of the development of thought and language. The social function of language develops starting from the earliest stages of infant development (from the phase of the syncretism to that of complex formation etc.) and, in particular, is realized within what Vygotskij defines natural forms, i.e. situations in which our experiences and our knowledge, our words, our speech etc. originate and which are the framework of experiential spaces (which are linguistic spaces too) from which all forms of culture and human communication follow. Tolstoj, especially the Tolstoj pedagogist, active in the school of Jasnaja Poljana, in this regard plays a central role, since, for him too, both the concepts and the words that give them a perceptible and coded form within an historical-natural language are related to natural forms of shared life, to complex games of interrelations with other human beings. The two authors differ, however, in how they consider the role of education and educators: Tolstoy thinks that the teacher may be just a “facilitator” of the innate abilities the child already possess, while Vygotskij thinks that the educator and, in general, the adult plays a fundamental role in the cognitive, linguistic and interactional development of the child